Collect like terms: 3x - x + 4x - 4y + 6y + 2 = 6x + 2y + 2
It is (4x + 2)
It is: 110x-2 simplified
4x + 20
x - 2
It is: 4x -34x^2 -21 simplified
It can be simplified to: 2x+2
(2x-1)(2x-1) = 4x^2 -4x + 1
It is a quadratic expression
Lets simplify the above given equation : -8 plus 6(-x - 3) plus 4x simplified as : -8-6x -18 +4x =-2x -26 . =-2(x+13).
It is: 10x+14 simplified
6x^2 +32x +12 -4x -3x^2 -36 = 3x^2 +28x -24 simplified
This expression can be simplified to: 2-6x
2x^3 - 3x^2 + 4x - 3
4x^2 = 16x 16x - 60x = -44x -44x + 225
The equation 4x + 5 = 2 has the solution 4x = -3 and x = - 3/4 (minus 3/4).
The answer to x4+x3-14x2+4x+6 divided by x-3 is x3+4x2-2x-2
Assuming there are no parentheses:2 times X - 1 + 4X - 6 + 2X =2X - 1 + 4X - 6 + 2X =2X + 4X + 2X - 1 - 6 =8X - 1 - 6 =8X - 7
4x2+4x-8 4(x2+x-2) and (4x+8)(x-1)
There is no equation, only an expression. An expression can be simplified but cannot be solved.